(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Higher education sector inOman has grown and made significant development in the last decade. There isheavy investment to improve the education infrastructure, provide increasededucation opportunities with focus on women education to ensure equality andequity. The spread of Higher Education Institutions (HEIs) of all types,diversified programmes and establishment of Quality Assurance Council is atestimony to the importance given by the nation to ensure quality of highereducation that the needs/requirements of 21st century are met. Inorder to achieve an international standard in higher education, all HEIs haveadopted - imported curriculum, recruited international / expatriate faculty andEnglish as a medium of instruction. Despite these efforts, the quality ofeducation in term of 21st century, requirement both in terms of knowledgeacquisition and skills seems to be missing and is not up to the desired level. This paper will discuss therole of quality assurance units in Higher Education Institutes. The discussionwill include an introduction on the need for Quality Assurance units followedby challenges facing quality assurance units. The paper then describes theoutcomes of an initial needs analysis that led to the development of a NationalQuality Plan. Some of the strategies in this plan for improving and increasingcapability are considered, most particularly the establishment of apractitioner‐oriented Oman QualityNetwork, and the design and implementation of a National Quality TrainingProgram. These two strategies attempt to address common obstacles tocapability, namely a paradigm that entrenches compliance and helplessness, andonly early awareness of effective quality enhancement and quality assuranceprinciples and methods.